Une controverse d’aménagement urbain relue par le prisme d’une didactique du paysage - Anne Sgard; Sylvie Paradis (Projets de Paysage)
The controversial Cherpines major urban planning project in the agglomeration of Geneva (Switzerland) was chosen as a case study for a research project on landscape didactics (20015-2018). This project is intended, based on the collective analysis of cases, to share ideas and didactic propositions concerning the landscape as a training tool. A workshop organised in November 2015, enabled the research-professors taking part to compare their perceptions and methods and to address a controversial issue from a different angle: analysing how it can be a relevant training object and propose pedagogical approaches for different audiences. The results of this exercise are briefly presented in an evaluation of the didactic potential of such a case study and a reflection on the question of training in landscape architecture through the landscape.